2012
DOI: 10.1155/2012/148616
|View full text |Cite
|
Sign up to set email alerts
|

The Problem of Confounding in Studies of the Effect of Maternal Drug Use on Pregnancy Outcome

Abstract: In most epidemilogical studies, the problem of confounding adds to the uncertainty in conclusions drawn. This is also true for studies on the effect of maternal drug use on birth defect risks. This paper describes various types of such confounders and discusses methods to identify and adjust for them. Such confounders can be found in maternal characteristics like age, parity, smoking, use of alcohol, and body mass index, subfertility, and previous pregnancies including previous birth of a malformed child, soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 37 publications
1
15
0
1
Order By: Relevance
“…Seasonal confounding has been identified as a potential source of bias in studies of the associations of exposures with birth outcomes, with the rate of prematurity and birth weight being dependent on season of conception (36, 37), although this potential bias may be only an artifact of the cohort truncation bias. Therefore, grouping pregnancies by pregnancy start date, care date, or trimester of vaccination may account for the 2 potential biases simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…Seasonal confounding has been identified as a potential source of bias in studies of the associations of exposures with birth outcomes, with the rate of prematurity and birth weight being dependent on season of conception (36, 37), although this potential bias may be only an artifact of the cohort truncation bias. Therefore, grouping pregnancies by pregnancy start date, care date, or trimester of vaccination may account for the 2 potential biases simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, even for women having a "non-indicated" IOL, there usually exist one or more risk factors that underlie the recommendation, or the request, for the IOL [51]. If women delivering after the spontaneous onset of labour are less likely to have risk factors than women having a "non-indicated" IOL, then the observational studies comparing the outcomes following IOL to the outcomes following spontaneous labour probably contain significant "confounding by indication" [52,53]. Finally, most of the observational studies that compared "non-indicated" IOL to spontaneous labour failed to correctly model the actual impact of ni_IOL on the flow of term pregnancy.…”
Section: Amor-ipat Exposed 2 Non-exposedmentioning
confidence: 99%
“…Even after the dramatic examples of diethylstilbestrol and thalidomide, in our opinion, it is urgent to increase the knowledge on drug effects in pregnant women through the use of multi-disciplinary research teams (obstetrics, pharmacologists, and so on); furthermore, it should be considered relative to the sex–gender of fetus. As sustained by the FDA, the inclusion of pregnant women in RCT is necessary to keep in mind that are many maternal and infant confounders [154]. Among infant confounders, it is necessary to recall the sex–gender of the fetus [155].…”
Section: Rulesmentioning
confidence: 99%